Five-minute Apgar score ≤ 5 and Molar Incisor Hypomineralisation (MIH) – a case control study. Issue 1 (December 2017) - Sidaly, Rivan; Schmalfuss, Andreas; Skaare, Anne; Sehic, Amer; Stiris, Tom; Espelid, Ivar
Abstract Background The aetiology of molar incisor hypomineralisation (MIH) is unclear. The asymmetric distribution of MIH in the dentition may indicate that an insult of short duration that affects ameloblasts at a vulnerable stage could be a causative factor. Apgar ≤ 5 at 5 min may indicate asphyxia (hypoxic-ischemic insult) during birth. It was hypnotised that low Apgar score during birth may cause MIH. The present study aimed to examine a possible association between Apgar ≤ 5 at 5 min and the occurrence of MIH. Method Two study groups were selected for examination. The cases comprised 67 children aged 8–10 years born with Apgar score equal to or below 5 after 5 min. The control group comprised 157 age-matched healthy children. First permanent molars, second primary molars and all permanent incisors were examined in all children. Clinical examination was undertaken by two calibrated examiners and intraoral close-up photographs of the teeth were later evaluated by three calibrated and blinded clinicians. Demarcated opacities, post-eruptive breakdown, atypical restorations and extractions due to MIH, according to the criteria of the European Association of Paediatric Dentistry, were assessed. Results The prevalence of MIH did not differ between the two groups. A chi-square test failed to confirm any statistically significant relationship between 5-min Apgar scores and MIH occurrence. In addition, there was no statistically significant relationship between the number of affected first permanent molars in cases and controls. Conclusion There was no association between Apgar ≤ 5 at 5 min and the occurrence of MIH.